2018
DOI: 10.1097/iae.0000000000001632
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Smoking on Macular Function and Structure in Active Smokers Versus Passive Smokers

Abstract: In the absence of clinically apparent foveal toxicity, CFT, SFCT together with ring amplitude ratio could be used as good predictors of subclinical nicotine induced foveal changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 31 publications
0
15
2
Order By: Relevance
“…In this study, a total of 13 observational studies (7 case-control, 5 cross-sectional, and 1 prospective consecutive case series study) were included [1628]. In the included studies, we identified a total of 614 smokers and 625 controls.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, a total of 13 observational studies (7 case-control, 5 cross-sectional, and 1 prospective consecutive case series study) were included [1628]. In the included studies, we identified a total of 614 smokers and 625 controls.…”
Section: Resultsmentioning
confidence: 99%
“…Cigarette smoking may cause retinal functional changes. El‐Shazly et al2018 reported that Ring 1 P1 amplitude was significantly lower in active smokers than passive smokers and longer in active smokers, compared to those of passive smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive retinal changes caused by tobacco have been widely demonstrated. Smokers were shown to have a significant decrease of the peripapillary RNFL [23], foveal thickness [24], the ganglion cell complex [25], and a significant decrease in the blood flow index of the choriocapillary plexus in the macular area [26]. In order to avoid any bias caused by the smoking habit, we carefully analyzed our samples and ascertained that the number of smokers was not significantly different between the groups.…”
Section: Discussionmentioning
confidence: 99%